Simultaneous twinning and microband formation under dynamic compression in a high entropy alloy with a complex energetic landscape. (November 2020) - Foley, D.L.; Huang, S.H.; Anber, E.; Shanahan, L.; Shen, Y.; Lang, A.C.; Barr, C.M.; Spearot, D.; Lamberson, L.; Taheri, M.L.
Abstract: High entropy alloys (HEAs) have been the subject of significant research in recent years due in part to their excellent mechanical properties and unique microstructure. Chemical disorder in these alloys is thought to lead to a complex energetic environment that affects the nucleation and movement of dislocations. In this study the development of deformation substructures is assessed in the Cantor HEA (CoCrFeMnNi) due to quasistatic and dynamic compression. Scanning and transmission electron microscopy (SEM/TEM) techniques are used to image and quantify dislocation density. When increasing the strain rate from 10 −3 s −1 to 5000 s −1 we observe an increase in the overall dislocation density which leads to the formation of deformation twins. Further at a rate of 8000 s −1, both deformation twins and microbands become operative plasticity modes, which are usually associated with different extremes of stacking fault energy. To relate this plastic response to chemical disorder, atomistic calculations are used to compute the generalized stacking fault energy curve and approximate the temperature dependence of the intrinsic stacking fault energy for the Cantor alloy, which reveals significant local variation in these critical energetic parameters associated with dislocation and twinning behaviors. Graphical abstract: Image, graphical abstract